Comparaison théorique sur la performativité de l’insulte homophobe. Austin, Bourdieu, Butler - Grégoire Ben-Aïssa (Glad!)
What does the homophobic (or racist, transphobic, misogynist, etc.) insult do to the person who receives it, and by virtue of what power relationship ? This question leads us to compare the approaches of Judith Butler and Pierre Bourdieu to the performativity and reappropriation of the insult. They transfer the notion of the performative from analytical philosophy to social and political philosophy, enabling us to understand the extent to which the insult, understood as an interpellation, can constitute its addressee as a stigmatised, excluded, dominated, precarious person, from a certain conventionality. They allow us to have a grasp on the circular economy of the homophobic insult. On the one hand, it is a form of domination or normativity that makes it possible ; on the other hand, the insult is one of the means of reproducing those power relationships. However, this reproduction is unequally guaranteed in our two authors’ theories, because of their divergent conceptions of repetition, which for Bourdieu rhymes with reproduction and reconduction and for Butler with iteration and alteration.